Microbial Production of Xylitol from Oil Palm Empty Fruit Bunch Hydrolysate: Effects of Inoculum and pH - Kresnowati, Made Tri Ari Penia; Setiadi, Tjandra; Tantra, Tan Mellisa; Rusdi, David (ITB Journal Publisher, LPPM ITB, 2016)
Considering its high content of hemicellulose, oil palm empty fruit bunch (EFB) lignocellulosic biomass waste from palm oil processing has the potential to be utilized as the raw material for the production of xylitol, a low calorie, low GI, and anti cariogenic alternative sugar with similar sweetness to sucrose. This research explored the possibility of converting EFB to xylitol via green microbial fermentation, in particular the effects of inoculum and initial pH on the fermentation performance. It was observed that the cell concentration in the inoculum and the initial pH affect cell growth and xylitol production. pH 5 was observed to give the best fermentation performance. Further, the fermentation tended to yield more xylitol at higher initial cell concentration. It was also observed that no growth or fermentation inhibitory compounds were found in the EFB hydrolysate obtained from enzymatic hydrolysis of EFB. Thus it can be used directly as substrate for xylitol fermentation.